Extending the DART model for social media. (1st January 2014) - Schiavone, Francesco; Metallo, Concetta; Agrifoglio, Rocco
The DART framework is one of the most appreciated theoretical arguments about the co-creation of new products and services by firms with the support of customers. In the internet age, companies very often started using web and social media in order to develop and/or design their new products and services with the support of users. This spread innovation approach made the DART framework somehow incomplete (at least for this form of co-creation) owing to its scant attention to technology. The aim of this study is to extend the traditional DART framework with a fifth dimension: technology management. The study reports the case of 'Lost in Google', a web-series of an Italian independent video-making company. The analysis shows that technology management is equally as important as the other four dimensions in order to manage properly co-creation by social media. A revised version of this model (DARTT) should fit better for the understanding of this phenomenon.